2022
DOI: 10.2147/hiv.s387190
|View full text |Cite
|
Sign up to set email alerts
|

Experiences and Perceptions on Community Client-Led ART Delivery (CCLADS) Model of Antiretroviral (ART) Delivery: Patients’ and Providers’ Perspectives in South Western Uganda

Abstract: Purpose Community Client-Led ART Delivery groups (CCLADS) were introduced as part of the differentiated service delivery models in 2017 to better serve growing number of HIV patients and reduce unnecessary burden on the HIV care delivery system. However, there is limited evidence on the exact patients’ and care providers’ experiences and perceptions regarding the CCLADS model of ART delivery. We therefore aimed to explore the experiences and perceptions on CCLADS model from the patient and provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 33 publications
1
5
1
Order By: Relevance
“…However, our multivariable analysis did not highlight any significant difference between PLHIV who received ART from peer CHW and those who received it directly at the clinic. This result contrasts with findings in certain other contexts where community-based delivery was associated with better treatment adherence 16 , 35 , 37 , 38 whether in times of crises or not 39 , 40 . This discrepancy may be explained by a fear of being recognized – and therefore stigmatized—as a PLHIV by persons in the general community if one were to go to an ART delivery point, something which has been observed in other contexts (e.g.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, our multivariable analysis did not highlight any significant difference between PLHIV who received ART from peer CHW and those who received it directly at the clinic. This result contrasts with findings in certain other contexts where community-based delivery was associated with better treatment adherence 16 , 35 , 37 , 38 whether in times of crises or not 39 , 40 . This discrepancy may be explained by a fear of being recognized – and therefore stigmatized—as a PLHIV by persons in the general community if one were to go to an ART delivery point, something which has been observed in other contexts (e.g.…”
Section: Discussioncontrasting
confidence: 99%
“…This discrepancy may be explained by a fear of being recognized – and therefore stigmatized—as a PLHIV by persons in the general community if one were to go to an ART delivery point, something which has been observed in other contexts (e.g. Uganda) 16 , 38 , 41 , 42 .…”
Section: Discussionmentioning
confidence: 99%
“…The findings are supported by Long et al 22 who pointed that peer-led ART delivery models are most likely to fail in communities where there exist other organizations with different motives. This is similar to documented experiences and perceptions on CCLADS Model from Patients' and Providers' Perspectives in South Western Uganda 23 . Many other scholars found similar results related to discrimination 20 .…”
Section: Discussionsupporting
confidence: 82%
“…Similar studies have shown that adherence rates were higher in groups where clients were involved in the distribution and administration of ART drugs than in those where healthcare providers were responsible for the entire process. 8 , 15 , 16 …”
Section: Discussionmentioning
confidence: 99%
“…This is due to the fact that transport costs can be a significant barrier to accessing healthcare services in many low-income countries. 8 Especially in rural and remote areas, clients may have to travel long distances to reach health facilities, which can be expensive. Our results are in agreement with evidence from elsewhere, where patients participating in the CCLAD model valued the opportunity to share the burden of ART refill pick-up transportation costs from facilities.…”
Section: Discussionmentioning
confidence: 99%